Diagnosis of Ovary-Containing Indirect Inguinal Hernia of the Canal of Nuck by Ultrasound (Journal of Enam Medical College, 2017)
In women, the round ligament is attached to the uterus near the origin of the fallopian tube, and a small evagination of parietal peritoneum accompanies the round ligament through the inguinal canal to the labium majorum. This small evagination of parietal peritoneum, named the canal of Nuck in women, is the equivalent of the processus vaginalis in men. Incomplete obliteration of the processus vaginalis causes indirect inguinal hernia or hydrocele of the canal of Nuck, a very rare condition in women. Here, we report a case of ovary-containing hernia of the canal of Nuck that was diagnosed with ultrasonography and was surgically confirmed. Gray scale and color Doppler ultrasonographic features studied were: the site and the size of the hernia, the texture of the hernia contents and the presence or absence of blood flow in the hernia contents.J Enam Med Col 2017; 7(1): 39-41